1994
DOI: 10.2466/pms.1994.78.3c.1385
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Changes in Length and Direction as a Cue for Perceived Depth

Abstract: A computer-generated configuration of three lines joined like hands on a clockface were perceived by 10 of 12 observers as having depth when the lines simultaneously changed in length and direction, thereby supporting Wallach, Adams, and Weisz's 1956 hypothesis regarding the necessary and sufficient conditions for a perceived kinetic depth effect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…To date, the efficacy of high-definition (HD) resolution in endoscopy has not been definitively proven [8], although it is commonly assumed, and every new available laparoscopy system on the market is equipped with HD technology. Spatial depth information loss in a 2D image can be compensated to a high degree by experience on the one hand [9], and by the ability of the human brain to interpret secondary spatial depth cues, such as shadows and parallax movement for estimation of spatial proportions [10][11][12][13][14], on the other hand. The benefit of secondary spatial depth cues focussing on shading was shown by Arrezzo et al [15].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the efficacy of high-definition (HD) resolution in endoscopy has not been definitively proven [8], although it is commonly assumed, and every new available laparoscopy system on the market is equipped with HD technology. Spatial depth information loss in a 2D image can be compensated to a high degree by experience on the one hand [9], and by the ability of the human brain to interpret secondary spatial depth cues, such as shadows and parallax movement for estimation of spatial proportions [10][11][12][13][14], on the other hand. The benefit of secondary spatial depth cues focussing on shading was shown by Arrezzo et al [15].…”
Section: Introductionmentioning
confidence: 99%
“…Humans gauge the distance to objects and their layout through a variety of depth cues, such as stereo parallax, motion parallax, eye accommodation, size, blocking, perspective, shadows, texture and brightness . Since the universal adoption of high‐definition (HD) cameras, the capture of texture, shadows and brightness as depth cues has improved substantially, such that the quality of laparoscopic images has advanced significantly in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In an empirical examination of this theoretical position, Brigner, Deni, and Hildreth (1) reported that observers perceive depth when presented simultaneous changes in the length and direction of lines configured like hands on a clockface. Since these changes in length and direction ostensibly provide a cue for perceiving depth, perhaps one can use these depth cues to generate a size illusion since there is theoretical argument that misleading depth cues lead to distortional illusions (2, 3 , pp.…”
mentioning
confidence: 97%